Striving Towards a Sustainable Solution: Water and Community in Veron, Dominican Republic - Bower, Erica (Consilience, 2012)
Access to clean and sanitized water is one of the most fundamental of Human Rights. However, in many communities around the world, water remains contaminated and a danger to human health. This photo essay seeks to outline an example of such circumstances in Domingo Maiz, shed light on the potential for a sustainable solution, and embody the cultural beauty of the local community.